Isolation of Helicobacter pylori from Gastric Biopsy of Dyspeptic Patients in Ghana and In Vitro Preliminary Assessment of the Effect of Dissotis rotundifolia Extract on Its Growth - Michael Buenor Adinortey; Charles Ansah; Cynthia Ayefoumi Adinortey; Ansumana Sandy Bockarie; Martin Tangnaa Morna; Damian H. Amewowor (Journal of Tropical Medicine)
Helicobacter pylori (H. pylori) is a gram-negative bacterium that colonizes the human stomach. Infection with this microaerophilic bacterium causes gastric and duodenal ulcer. This study sought to isolate H. pylori, from gastric biopsy samples of dyspeptic patients in Ghana using a 2,3,5-triphenyltetrazolium chloride (TTC) dye incorporated medium method. This TTC dye method was further used in an antimicrobial susceptibility assay involving Dissotis rotundifolia extract (DRE). H. pylori were successfully isolated from gastric biopsy of dyspeptic patients. Pure cultures of H. pylori in 2,3,5-triphenyltetrazolium chloride (TTC) dye incorporated medium were seen as sparkling colonies. Isolates, identified as H. pylori, were gram-negative and urease, catalase, and oxidase positive and showed characteristic morphology as spiral-shaped bacteria under the microscope. The organisms were found to be susceptible to cephalothin and resistant to nalidixic acid. Above all, the observation that H. pylori grew only at 37°C and not 25°C or 42°C affirms that the bacterium is neither Helicobacter cinaedi nor Helicobacter fenneliae. The anti-H. pylori study depicts a statistically lower zone of inhibition for DRE compared to standard drugs [amoxicillin and clarithromycin] (p<0.05), whereas metronidazole showed no zone of inhibition. This study reports the first successful isolation and culturing of H. pylori in Ghana using TTC dye. It also shows that DRE possess an in vitro anti-H. pylori activity and that DRE has some therapeutic potential against H. pylori infection.